A secured data transform-and-transfer algorithm for energy internet-of-things applications - Abbas M. Al-Ghaili; Hairoladenan Kasim; Naif Mohammed Al-Hada (Universitas Ahmad Dahlan, 2021)
Digital transformation (DT) is one of the key technologies with effective impacts on many traditional processes towards a digital world. DT influences the way other digital services behave. Hence, there is a need to consider DT-related processes carefully specifically while designing phase. DT contributes to many services. It can, for example, contribute to implement security tasks applied to digital contents and therefore can be applied to change contents being secured. One of the transformation ways applied in security is to consider the way those digital contents are being stored or transferred. This paper proposes a DT algorithm (DTA) for energy internet-of-things (EIOT) contents. DTA consists of two steps, to convert original contents to another digital form and to transfer that form utilizing IOT. This paper utilizes DT in term of security. EIOT contents are converted to increase security. It is aimed to transfer EIOT contents to destination safely and efficiently. Thus, EIOT contents are transformed first to hide original contents. To make sure that the transferring process is done safely, DTA is evaluated in terms of efficiency, accuracy, and robustness. Results confirm that DTA is efficient, accurate, and robust against loss of bits caused by transferring.